Encapsulation of Lemongrass Oil for Antimicrobial and Biodegradable Food Packaging Applications - Can, Fidan Ozge; Durak, Muhammed Zeki (AMER SCIENTIFIC PUBLISHERS, 2021)
Antimicrobial gelatin nanofibers with lemongrass essential oil (Gt/LEO) were successfully fabricated by electrospinning as potential biodegradable and active food packaging. Following the determination of the key components and the composition of the LEO by a Gas chromatography-mass spectrometry (GC-MS) headspace analysis, the antimicrobial activity of LEO was tested against four different bacteria. Gt/LEO solutions were prepared and characterized before the electrospinning process. All the prepared solutions could be electrospun, and the effect of LEO on electrospinnability was investigated by measuring conductivity, surface tension, and dielectric constant. The average diameter of pure gelatin nanofibers was 110 +/- 39 nm and increased with the rise in essential oil content, similar to other studies. The structure of all nanofibers was smooth, stable, homogenous, and bead-free. The maximum growth inhibition rate (GIR) of Gt/10% LEO nanofilms was 99.09% against Staphylococcus aureus and 96.63% for Salmonella Typhimurium. Nanofilms incorporated with and without LEO displayed similar major Fourier transform infrared (FTIR) spectroscopy peaks showing the effective penetration of LEO in gelatin fibers without chemical interaction or destroying the structure of LEO or gelatin. Thermal analyses indicated that thermal stability of the essential oil enhanced by encapsulation. Overall, this study demonstrates that Gt/LEO nanofibers have a promising prospect in the area of antimicrobial food packaging.
Keywords: Food Packaging; Electrospun Nanofibers; Essential Oil Encapsulation; Gelatin; Biodegradable Package; INCLUSION COMPLEX; IN-VITRO; NANOFIBERS; FILMS; ZEIN; Science & Technology - Other Topics; Materials Science; Physics